2022
DOI: 10.3390/healthcare10122384
|View full text |Cite
|
Sign up to set email alerts
|

Do You Feel Safe at Home? A Qualitative Study among Home-Dwelling Older Adults with Advanced Incurable Cancer

Abstract: Many older adults with cancer prefer to live at home, and home treatment and outpatient care have been recommended for such patients. To improve their mental health, it is important to identify the challenges that are faced by home-dwelling older adults with cancer. This study aimed to examine the impact of the home on older adults with advanced cancer who were receiving treatment and follow-up care. In a cross-sectional design with criterion-based sampling, eight qualitative interviews were transcribed and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Feeling unprepared for their new role as carers and lacking information and knowledge were some of the greatest obstacles reported by those walking on this lesstravelled road. The feeling of being unprepared for the caregiver role is in line with other studies on end-of-life care and is not limited to rural areas [4,17,51,52]. Not knowing what to expect around the next bend of the road while carrying the heavy load of responsibility is interpreted as a double burden in our meta-ethnography.…”
Section: Discussionsupporting
confidence: 80%
“…Feeling unprepared for their new role as carers and lacking information and knowledge were some of the greatest obstacles reported by those walking on this lesstravelled road. The feeling of being unprepared for the caregiver role is in line with other studies on end-of-life care and is not limited to rural areas [4,17,51,52]. Not knowing what to expect around the next bend of the road while carrying the heavy load of responsibility is interpreted as a double burden in our meta-ethnography.…”
Section: Discussionsupporting
confidence: 80%
“…A previous study conducted in Hunan Province, China, showed that nurses were concerned about the safety of patients and their own practice during home visits [ 44 ]. Furthermore, some relevant studies had also reported the need to enhance the safety management of home care [ 45 , 46 ]. The six items in the safety practice dimension of this study included risk identification, use of the APP locator system, wearing an alarm device, occurrence of patient accidents, medical staff safety accidents, and requesting support, with the lowest scores for the items using the APP locator system and wearing an alarm device, which was in line with the results of other researchers [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such words indicate an affective bond between people and their homes, which relates to both the fundamental character of the home itself and the meaning people assign to it. 15,24 This bond between person and home is a common finding in studies related to the meaning of home. For example, Hilli and Erikson 25 claimed that being home entailed being at home in oneself.…”
Section: Introductionmentioning
confidence: 92%